Spatial variation in high-frequency oscillation rates and amplitudes in intracranial EEG - Guragain, Hari; Cimbalnik, Jan; Stead, Matt; Groppe, David M; Berry, Brent M; Kremen, Vaclav; Kenney-Jung, Daniel; Britton, Jeffrey; Worrell, Gregory A; Brinkmann, Benjamin H (Neurology, 2018)
OBJECTIVE: To assess the variation in baseline and seizure onset zone interictal high-frequency oscillation (HFO) rates and amplitudes across different anatomic brain regions in a large cohort of patients. METHODS: Seventy patients who had wide-bandwidth (5 kHz) intracranial EEG (iEEG) recordings during surgical evaluation for drug-resistant epilepsy between 2005 and 2014 who had high-resolution MRI and CT imaging were identified. Discrete HFOs were identified in 2-hour segments of high-quality interictal iEEG data with an automated detector. Electrode locations were determined by coregistering the patient's preoperative MRI with an X-ray CT scan acquired immediately after electrode implantation and correcting electrode locations for postimplant brain shift. The anatomic locations of electrodes were determined using the Desikan-Killiany brain atlas via FreeSurfer. HFO rates and mean amplitudes were measured in seizure onset zone (SOZ) and non-SOZ electrodes, as determined by the clinical iEEG seizure recordings. To promote reproducible research, imaging and iEEG data are made freely available (msel.mayo.edu). RESULTS: Baseline (non-SOZ) HFO rates and amplitudes vary significantly in different brain structures, and between homologous structures in left and right hemispheres. While HFO rates and amplitudes were significantly higher in SOZ than non-SOZ electrodes when analyzed regardless of contact location, SOZ and non-SOZ HFO rates and amplitudes were not separable in some lobes and structures (e.g., frontal and temporal neocortex). CONCLUSIONS: The anatomic variation in SOZ and non-SOZ HFO rates and amplitudes suggests the need to assess interictal HFO activity relative to anatomically accurate normative standards when using HFOs for presurgical planning.
Keywords: Seizures; počítačová rentgenová tomografie; Magnetic Resonance Imaging; Signal Processing, Computer-Assisted; mozek; magnetická rezonanční tomografie; Humans; mapování mozku; kohortové studie; Drug Resistant Epilepsy; Female; elektrokortikografie; záchvaty; počítačové zpracování signálu; lidé; Periodicity; Cohort Studies; periodicita; Brain Mapping; refrakterní epilepsie; ženské pohlaví; Male; Tomography, X-Ray Computed; Brain; předoperační péče; Preoperative Care; mužské pohlaví; Electrocorticography